A comparative anatomical investigation of three taxa of Brassica L. from Bangladesh (Bangladesh Journal of Plant Taxonomy, 2020)
In the present study, micromorphology and comparative anatomy of young root, stem and leaf of three economically important taxa of Brassica L. viz., B. rapa L. subsp. campestris (L.) Clapham, B. juncea (L.) Czern. and B. napus L. are investigated in detail for the first time in Bangladesh by using light microscopy (LM). In anatomical studies, cross sections of young root, stem and leaf have been examined and biometric measurement of cell and tissues are presented. The micromorphological studies are related to the epidermal surface. In addition, the stomatal index and stomatal index ratio of these taxa have been calculated and presence of simple, non-glandular, unicellular trichome on stems and leaves also been observed except on the stem of B. rapa L. subsp. campestris (L.) Clapham. The anatomical study reveals that the investigated taxa have primary growth in roots and stems as well as amphistomatic and bifacial leaves with anisocytic stomata have been noticed. Finally, presence of tetrarch or single strand exarch xylem in vascular bundle of root, the size, shape and presence or absence of trichome over stem, shape of midrib of leaf have been considered to provide reliable features for identification of the Brassica species.Bangladesh J. Plant Taxon. 27(1): 15-26, 2020 (June)